Sustainable Energy Demand in Bangladesh: The Influence of Financial and Political Factors through Marshallian Demand Function - Ulfat, Tasnova Jerin; Bala, Shewly; Prathibha, H.; Cherian, Ann Mary; Hossain, Hemel; Ridwan, Mohammad; Ridzuan, Abdul Rahim; Mukthar, K.P. Jaheer (International Journal of Energy Economics and Policy, 2025)
The study aims to consider the impact of economy, trade openness (TRD), political stability (POS), financial development (FD), and urbanization (URB) on the energy demand (ENU) of Bangladesh. Several techniques, including the ARDL bound test for cointegration, DOLS, FMOLS, and CCR, were used to check how changes in independent factors impacted the dependent parameter. The ARDL findings indicate a considerable encouraging correlation among GDP expansion, political stability, trade openness, urbanization, and ENU. A 1% rise in GDP, POS, TRD, and URB causes a long-term rise in energy utilization of 0.327%, 0.817%, 1.166%, and 1.775%, respectively. In contrast, the increase in FD has a substantial favorable correlation with ENU, with energy use anticipated to decrease by 0.192% in the long term for every 1% upsurge in FD. The reliability of the findings is further validated by multiple estimators, including FMOLS, DOLS, and CCR. The Pairwise Granger Causality assessment was adopted to show the causal connection among many components. The analysis advocates for the establishment of regulatory initiatives to encourage energy efficiency, enhance the use of green power, and invest in sustainable trade and urban planning to reduce energy use and attain sustainable cities and environments in Bangladesh.